ELECTRODEPOSITION OFNIW ALLOY AS AN ANTICORROSION COATING - Elyasta Sebayang, Stevanus
NiW alloy has a potential to be a coating metal to prevent corrosion in a substrate. This is caused by the propertise of nickel and tungstate which are known to withstand corrosion and has good mechanical propertise. Tllis study observed the corrosion resistance propertise in NiW alloy to environmental changes in comparison to pure Ni coating. Electrodeposition technique is chosen as the method to coat metal substrate with NiW alloy, due to its abilities to produce homogenized alloy with smooth surface. Electrodeposition is done in two hours with 0.1 A.cm•2 current density and 1.2 V potential, with citrate ion as metal ion complexing agent. The substrate coated with NiW alloy is being characterized by XRD dan SEM-EDS and the its corrosion resistance is being measured by EIS (Electrochemical Impedance Spectroscopy) method. The EIS measurement is done by varieting the NaCI concentration (1%, 2%. and 3%) in aqueous HCI I M to observe the corrosion resistance in environmental changes. XRD characterization result shows that the electrodeposition of NiW alloy has successfully completed by the appearance of a peak in 2e by 43.38° (111 ); 50.58° (200) and 74.25% (220). Characterization by SEM-EDS showed that Ni atom and W are detected in the deposition layer with 7.02% mole of W. Measurement with EIS showed that NiW alloy has better coiTotion resistance than pure Ni coating showed by the bigger Ret point in any condition, with resistance efficiency to Ni coating in l %, 2%. 3% NaCI and resistance to 1 M HCI by 26.72%; 48.23%; 52.25% and 39.74% respectively.